THE EFFECT OF A COGNITIVE-BEHAVIORAL COUNSELING PROGRAM ACCORDING TO PSYCHOLOGICAL ALIENATION TO REDUCE THE FEELING OF PSYCHOLOGICAL EXHAUSTION AMONG YOUNG WEIGHTLIFTERS - Assoc. Prof. Haider Kazem Abdel Zahra (Proximus Journal Publishing, 2024)
The importance of the research lies in shedding light on the study of the psychological state of the players and the various psychological pressures they are exposed to that may lead them to psychological exhaustion and thus their inability to continue training and reach higher levels. As for the problem of the research, the researcher wanted to study the feeling of psychological exhaustion among players who are under pressure, which has negative effects on the shoulders of the individual, which results in his withdrawal from training .The research aimed to build a psychological exhaustion scale for weightlifters (youth), while the research areas included the human field, which was represented by the players of the southern and central region (weightlifting), and the time range was determined for the period from (15/8/2023) until (15/11/2023), while the spatial field was in the halls of the clubs studied.The researcher used the experimental approach in the style of the two groups as well as the descriptive approach, and the research sample consisted of (77) players, and the (SPSS) system was used to obtain the results of the research, and the researcher concluded the following
Keywords: Counseling Program; Psychological Alienation; Burnout